A voz que “salva”: a persuasão por meio da prosódia e da argumentação no discurso radiofônico de padre Marcelo Rossi - Cruz, Regiane Aparecida da (2009)
This research aims at analyzing how prosody corroborates the argumentative elements in the discourse of Priest Marcelo Rossi, a charismatic representative of the catholic church. For this analysis, we have selected as corpus one session of the radio show “Moment of faith” entitled “The Journey”. The religious discourse in the radio has drama as a relevant characteristic and voice is a fundamental device in the persuasive process. This is why we have set the hypothesis that the speaker is aware of his voice performance as a role in the discourse and thus he creates, in the sermon, a performance joined to the rhetorical arguments in order to reach his main goal: his audience’s support. By using as theory the prosody, which in current linguistics refers to the phonetical phenomena set based on the suprasegment of phonemes, we have selected four elements for the analysis: pitch and voice quality, which refer to melodic pitch variation; volume, which refers to intensity variation; and pause, which refers to duration variation. All have been analyzed in its pragmatics function, which is about the speaker’s attitudes and which varies according to his intention. In order to develop this research, we have found the theoretical linguistic approach in Perelman and Olbrechts-Tyteca (2005); Reboul (2004); Aristotles (s/d); Cagliari (1992) and Bollela (2006). The data collection and the transcription of the lectures were made with the help of softwares such as Praat 4.6.12 and Sound Forge 8.0. We have learned that our speaker’s discourse is built up over his ethos, a pre conceived image of a “young devout up-to-date priest”. We have also found out that there is a constant concern on maintaining this image. Due to such image, Priest Rossi keeps developing his “Journey” engaged on passions. These passions are mainly unleashed by the use of the rethoric figure called Hipotipose, which consists on a zealous emotional description of something or someone in order to remind his audience of an image by mentally representing or projecting it. Besides, we have concluded that the rhetoric-argumentative elements present in the priest’s discourse are tied together and keep a relationship of interdependence with the prosodic resources. We could confirm that Priest Rossi’s discourse lies on emotion, on the belief already established of his private audience, and that his prosody is fundamental in the “do-believe” discourse because it helps overcome the physical absence of the speaker during the discoursive process. Key words: Prosody; Argumentation; Religious Discourse; Persuasion.